3D Texture Analysis of the Corpus Callosum in T1-Weighted MR Images of Children with a Traumatic Brain Injury - Jan Novak; Ahmed E. Fetit; Daniel Griffiths-King; Cathy Catroppa; Vicki A. Anderson; Amanda G. Wood (Brain Topography, 2026)
Investigating traumatic brain injuries (TBI) in the developing brain is a challenging task. The superposition of an injury to the normal development trajectory can lead to brain impairments which are not obvious at diagnosis. T1-weighted MRI, acquired routinely post-injury, has the potential to better inform diagnosis, but is limited by qualitative assessment by radiologists. Using T1-weighted volume images, we investigated the use of three-dimensional texture analysis (TA) on regions of the corpus callosum (CC) in children with TBI and typically developing controls (TDCs) in conjunction with analysis of diffusion weighted image (DWI)-derived metrics. Nineteen TDCs and 37 participants with TBI were included in the study. T1 textural metrics were extracted from the splenium, genu and body of the CC and assessed for differences between the groups. Textural skewness was found to be significantly higher in children with TBI than TDCs in the body of the CC (t-test: p < 0.004, effect size: g = 0.91) and significant differences were observed in the genu of the CC (grey level co-occurrence matrix and Grey-level run length matrix, p < 0.004, effect sizes > 0.6). Non-significant reductions in ADC were found between TBI and TDC groups in the body and the splenium of the CC. Interestingly, no differences were found between TDCs and the TBI sample using FA. The results suggest that TA can potentially be used to assess white matter integrity after paediatric TBI.